Sequence-selective binding of oligonucleotides to superparamagnetic cobalt ferrite nanoparticles: a new way to fabricate functional nanoconjugates; RSC Advances; Iss. 33 - Pershina A. G. Aleksandra Gennadievna; Ogorodova L. M.; Magaeva A. A.; Itin V. I.; Naiden E. P.; Izaak T. I.; Shchegoleva N. N.; Sazonov A. E. (2015, 2015)
Title screen